Argentinian consumers' extra virgin olive oil preference - Pardo, J. E.; Álvarez-Ortí, M.; Araniti, V.; Bauzá, M.; Rubio, M.; Zied, D. C. [UNESP]; Silvestre, A. (My University, 2018)
Olive oil has been introduced in many regions with Mediterranean climate around the world. However, many of these areas have not yet implemented an adequate olive oil culture. In this work, the preferences of Argentinian consumers have been studied with respect to extra virgin olive oil, to evaluate consumers' behaviour in regions with a different olive oil culture. With this purpose, three extra virgin olive oils with different purity and quality were purchased. Tasting sessions with 100 consumer judges took place in two Argentinian provinces with a different olive cultivation tradition (Buenos Aires and Mendoza). The oils were subjected to sensory evaluation by consumers (test for measuring the degree of satisfaction by using verbal hedonic scale). The results differed depending on the province. In Mendoza, with greater olive oil tradition, the olive oil of highest quality was the best valued, while in Buenos Aires, the preferred olive oil was the one with the lowest quality and probably mixed with other seed oils.
Keywords: Argentina; Consumer; Olive oil; Quality; Sensory